Biomonitoring the skeletal muscle metabolic dysfunction in knee osteoarthritis in older adults: Is Jumpstart Nutrition® Supplementation effective? - Apurba Ganguly; Banerjee Sudip (Babol University of Medical Sciences, 2023)
Background: This study aimed to investigate the efficacy of Jumpstart Nutrition® dietary supplement (JNDS) for enhancing the skeletal muscle metabolism and function of older adults with knee osteoarthritis (KOA) by evaluating the biomarkers of aberrant levels of serum tumor necrosis factor-alpha (TNF-α), interleukin-10 (IL-10), C-reactive protein (CRP), creatine kinase-muscle (CK-MM), and aldolase-A (Aldo-A). Methods: This twelve-week registry included 54 patients treated with JNDS mainly comprised of calcium, phosphorus, vitamin-K2, coenzyme-Q10, boswellic acid, and curcumin mixed with soy and whey protein (experimental group) and 51 patients treated with symptomatic slow-acting drugs for osteoarthritis (SYSADOA) (control group) for KOA confirmed with radiological images. At week 0 and week 12 for both the groups evaluated, the non-fasting serum levels of TNF-α, IL-10, CRP, CK-MM, and Aldo-A by using appropriate kits. Results: At week-twelve, the respective values of area under the ROC curves of the studied biomarkers for pooled experimental cohorts were 0.928, 0.907, 0.908, 0.927, and 0.988 having the significance of accuracy (R-square):66.28%, 47.25%, 70.39%, 65.13%, and 68.00%, indicating a satisfactory treatment policy, their mean± SD, and risk ratio, all exhibited highly significant differences (p<0.0001) and KOA-gradation was upgraded between≥2 and ≥3 from≥4 as per the Kellgren-Lawrence  scale compared to the control. Fewer patients had to use emergency medications (p<0.05). Conclusions: Results suggest that JNDS may be effectively used to strengthen the skeletal muscle metabolism and function of elderly patients with KOA confirmed with the stabilization of studied biomarkers as an alternative to the treatment of SYSAD correlated with ROC curves and the Kellgren-Lawrence scale.